The clock gene Per1 is necessary in the retrosplenial cortex—but not in the suprachiasmatic nucleus—for incidental learning in young and aging male mice - Brunswick, Chad A.; Baldwin, Derek J.; Bodinayake, Kasuni K.; McKenna, Alexandria R.; Lo, Chen-Yu; Bellfy, Lauren; Urban, Mark W.; Stuart, Emily M.; Murakami, Shoko; Smies, Chad W.; Kwapis, Janine L. (Neurobiology of aging, 2023)
•Learning induces Per1 expression within the RSC of young and aging mice.•This RSC Per1 induction rhythmically cycles in young and aging mice.•Bidirectional RSC Per1 manipulations affect spatial memory.•Learning also induces Per1 within the SCN of young (but not aging) mice.•Per1 knockdown in the SCN of young mice has no effect on memory. Aging impairs both circadian rhythms and memory, though the relationship between these impairments is not fully understood. Circadian rhythms are largely dictated by clock genes within the body's central pacemaker, the suprachiasmatic nucleus (SCN), though these genes are also expressed in local clocks throughout the body. As circadian rhythms can directly affect memory performance, one possibility is that memory deficits observed with age are downstream of global circadian rhythm disruptions stemming from the SCN. Here, we demonstrate that expression of clock gene Period1 within a memory-relevant cortical structure, the retrosplenial cortex (RSC), is necessary for incidental learning, and that age-related disruption of Period1 within the RSC—but not necessarily the SCN—contributes to cognitive decline. These data expand the known functions of clock genes beyond maintaining circadian rhythms and suggests that age-associated changes in clock gene expression modulates circadian rhythms and memory performance in a brain region–dependent manner.